TWO FETAL DEMISES IN TRIPLETS PREGNANCY IN SECOND TRIMESTER WITH IMPLICATIONS ON LIVE FETUS AND MOTHER’S HEALTH - Livrinova, Vesna; Simeonova Krstevska, Slagjana; Kamiloska, Martina; Dimitrovska, R; Karadjova, Dafina (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2024)
Triples pregnancies is when three fetuses are carried and delivered by mother at once. The over all incidence is 1of 7,300 pregnancies. As a result of the use of aided reproductive technology, the overall incidence of these pregnancies has increased. They are with increased perinatal risks because of intrauterine growth restriction, fetal discordance, intrauterine demise, congenital malformations, preterm birth, pre-eclampsia, gestational diabetes, anemia, risk for thrombosis, operative and anesthesiology complications.The main goal of this case report is presenting the implications of intrauterine dead of two fetuses in triplets conceived spontaneously at 25 gesta tional weeks. It was the second pregnancy after the earlier cesarean section. The ultrasound scan at our clinic revealed diamniotic, dichorionic pregnancy with fused placentas at 23 gestational weeks with three live discordant fetuses more than 20% between them with amount of amniotic fluid in normal range. At the next control scan two weeks later, one fetus was dead and after 4 days the other one died in the same amniotic sac. In 26th gestational week, iatrogenic prema ture delivery with second cesarean section in regional anesthesia was done. A vital male fetus with 1,050g and 31cmand two dead fetuses were delivered.The discordance between them was 9.2% and it was 40% with a live fetus. After 10 weeks the live newborn was discharged without serious sequels. It can be concluded that it is especially important to detect multi fetal pregnancy as soon as possible, especially number of fetuses, chorionicity and amnionicity, to prevent the above-mentioned complications.
Keywords: demise; fetal; implication; maternal; triplets